PERAN MAHASISWA KKN DALAM PENDIDIKAN BAGI MASYARAKAT YANG TERDAMPAK COVID-19 DI DESA HAMPARAN PERAK - Khairunnisa Khairunnisa; Nabilah Azmi; Hasrat Effendi Samosir (PKM-P, 2022)
ABSTRACT The purpose of this research is to help communities affected by Covid-19 in Hamparan Perak Village to learn and ease the burden on parents who have difficulty guiding their children to take part in online learning. This activity is carried out by providing tutoring (bimbel) or an association that students can join to study together. The object of this research is students in Hamparan Perak Village, North Sumatra, with an age range of 5-12 years. Using the observation and literature method, the research begins by identifications, means collecting data on the number of students to be taught and their conditions, which ultimately results in the fact that many students cannot read and recognize numbers. The results of the activity of this student study service were quite positive, namely providing teaching on calistung (baca, tulis, hitung), and English. Key Word: Role, Covid-19, Tutoring